Hypoxia and exercise increase the transpulmonary passage of 99mTc-labeled albumin particles in humans. - Melissa L Bates (Public Library of Science (PLoS), 2014)
Intrapulmonary arteriovenous anastomoses (IPAVs) are large diameter connections that allow blood to bypass the lung capillaries and may provide a route for right-to-left embolus transmission. These anastomoses are recruited by exercise and catecholamines and hypoxia. Yet, whether IPAVs are recruited via direct, oxygen sensitive regulatory mechanisms or indirect effects secondary to redistribution pulmonary blood flow is unknown. Here, we hypothesized that the addition of exercise to hypoxic gas breathing, which increases cardiac output, would augment IPAVs recruitment in healthy humans. To test this hypothesis, we measured the transpulmonary passage of 99mTc-macroaggregated albumin particles (99mTc-MAA) in seven healthy volunteers, at rest and with exercise at 85% of volitional max, with normoxic (FIO2 = 0.21) and hypoxic (FIO2 = 0.10) gas breathing. We found increased 99mTc-MAA passage in both exercise conditions and resting hypoxia. However, contrary to our hypothesis, we found the greatest 99mTc-MAA passage with resting hypoxia. As an additional, secondary endpoint, we also noted that the transpulmonary passage of 99mTc-MAA was well-correlated with the alveolar-arterial oxygen difference (A-aDO2) during exercise. While increased cardiac output has been proposed as an important modulator of IPAVs recruitment, we provide evidence that the modulation of blood flow through these pathways is more complex and that increasing cardiac output does not necessarily increase IPAVs recruitment. As we discuss, our data suggest that the resistance downstream of IPAVs is an important determinant of their perfusion.